Faktor-faktor yang Mempengaruhi Perilaku Menyontek Siswa SMK Negeri 10 Semarang - Rofiq, M. Ainnur; Fitriana, Siti; Ismah (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
This study focuses on the factors that affect the cheating behavior of students at SMKN 10 Semarang with the number of subjects in this study as many as 15 people, including 11 students and 4 teachers. This study uses a qualitative approach to case studies. Toobtain data in this study, interviews were used. The results of the research obtained are factors that affect the cheating behavior of SMKN 10 Semarang students, including parental demands, procrastination, lack of understanding of the material, opportunities, peers. To guidance and counseling teachers to be more serious about overcoming and guiding students who behave in cheating behavior by using various services and approaches. It also provides more educational and appropriate punishments/sanctions to students, which aims to show student awareness. It is recommended to guidance and counseling teachers to coordinate and cooperate with school principals, homeroom teachers, subject matter teachers and parents/guardians to deal with students who behave cheating.